Terrorism discourse in popular Arab media: Representation of the Taliban in CNN Arabic youtube headlines - Annisa Khairunnisa; Hetti Waluati Triana; Reflinaldi; Said Ibnu Shina (Diwan: Jurnal Bahasa dan Sastra Arab, 2025)
In August and September 2021, the Taliban emerged as a prominent subject in many media during the Afghan leadership transition. While prior research has examined the media's portrayal of the Taliban from diverse viewpoints and methodologies, no investigation has concentrated on their representation as the actor in the discourse.  This study aims to investigate the representation of the Taliban in mainstream media, thereby addressing the existing research gap. The Taliban news headlines from the CNN Arabic YouTube channel, from August to September 2021, were utilized as data sources in a qualitative-descriptive study methodology. Theo van Leeuwen's discourse analysis was employed to delineate actor representation by mapping inclusion and exclusion tactics. The findings demonstrate that CNN Arabic employs exclusion and inclusion in its representation of the Taliban. Exclusion arises in strategy nominalisation, whereas inclusion occurs in strategies of identification, abstraction, determination, differentiation, and categorization. CNN Arabic depicts the Taliban unfavourably through a severe and hyperbolic storyline. This representation is grounded in political objectives aimed at steering public discourse and provoking insurrection against the Taliban. These findings enhance media discourse analysis by identifying the Taliban as the primary actor, hence expanding the comprehension of representation tactics employed to influence public perception. This study highlights the importance of critical media literacy, particularly in understanding the interplay between ideology, political objectives, and the representation practices of actors in international conflict reporting.